Impact of the Timing of Enzyme Replacement Therapy Initiation and Cognitive Impairment Status on Outcomes for Patients with Mucopolysaccharidosis II (MPS II) in the United States: A Retrospective Chart Review - Karen S. Yee; David Alexanderian; Yidie Feng; Xiaowei Ren; Bernd Schweikert; Olulade Ayodele (Journal of Health Economics and Outcomes Research)
**Background:** Mucopolysaccharidosis II (MPS II; Hunter syndrome; OMIM 309900) is a rare, X-linked, lysosomal storage disease caused by deficient iduronate-2-sulfatase activity. Accumulation of glycosaminoglycans results in multisystemic disease manifestations, which may include central nervous system involvement and cognitive impairment (CI). Patients with MPS II experience a high disease burden, leading to extensive healthcare resource utilization (HRU) and reduced quality of life.